Harnessing the CRISPR-Cas Systems to Combat Antimicrobial Resistance - Duan, Cheng; Cao, Huiluo; Zhang, Lian-Hui; Xu, Zeling (Frontiers in Microbiology, 2021)
The emergence of antimicrobial-resistant (AMR) bacteria has become one of the most serious threats to global health, necessitating the development of novel antimicrobial strategies. CRISPR (clustered regularly interspaced short palindromic repeats)-Cas (CRISPR-associated) system, known as a bacterial adaptive immune system, can be repurposed to selectively target and destruct bacterial genomes other than invasive genetic elements. Thus, the CRISPR-Cas system offers an attractive option for the development of the next-generation antimicrobials to combat infectious diseases especially those caused by AMR pathogens. However, the application of CRISPR-Cas antimicrobials remains at a very preliminary stage and numerous obstacles await to be solved. In this mini-review, we summarize the development of using type I, type II, and type VI CRISPR-Cas antimicrobials to eradicate AMR pathogens and plasmids in the past a few years. We also discuss the most common challenges in applying CRISPR-Cas antimicrobials and potential solutions to overcome them.